Experimental trial of bioencapsulation of antimicrobial agent for the treatment of bacterial etiology diseases in seabass (Dicentrarchus labrax) fry. Evaluation of different therapeutic regimes - MOURELATOS (Σ. ΜΟΥΡΕΛΑΤΟΣ) S.; TOURAKI (Μ. ΤΟΥΡΑΚΗ) M.; SAVVIDIS (Γ. ΣΑΒΒΙΔΗΣ) G.; SOULOUNIAS (Γ. ΣΟΥΛΟΥΝΙΑΣ) G.; KASTRITSIS (Κ. ΚΑΣΤΡΙΤΣΗΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Early stages of larval development of seabass and seabream are typically fed with live feeds (nauplii of Artemia). The different disease of microbial etiology with important economic consequences, constitute one of the most significant problems during this first larval period. Therapeutic interventions, implying oral delivery of appropriate antimicrobial agents, are considered more feasible and environmentally friendly. The method used consists in techniques of bioencapsulation (incorporation of therapeutics in the live feeds). In specially designed facilities of the Laboratory of General Biology, School of Biology, Aristotle University of Thessaloniki, in the frame of a European Union research programme, experimental trials were carried out on seabass fry with Vibrio anguillarum strains, aiming at the optimisation of therapeutic and/or preventive schemes. Within this work, comparative results from separate experimental sets (each set comprising eight different experimental series [conditions], each series having five aliquots) are presented. The experimentation will be continued by using different strains and different bacterial species and by testing other relevant experimental protocols.